Cerebral Venous Thrombosis Revealing Primary Sjögren Syndrome: Report of 2 Cases. (3rd January 2013) - Mercurio, A.; Altieri, M.; Saraceni, V. M.; Paolucci, T.; Lenzi, G. L.
Abstract : Sjögren syndrome (SS) is an autoimmune disease of the exocrine glands, characterized by focal lymphocytic infiltration and destruction of these glands. Neurologic complications are quite common, mainly involving the peripheral nervous system (PNS). The most common central nervous system (CNS) manifestations are myelopathy and microcirculation vasculitis. However, specific diagnostic criteria for CNS SS are still lacking. We report two cases of primary SS in which the revealing symptom was cerebral venous thrombosis (CVT) in the absence of genetic or acquired thrombophilias.